Christmas : a Candid History. - Forbes, Bruce David (University of California Press, 2007)
Presents an entertaining perspective on how the annual Yuletide celebration got to be what it is today. This book tells the story of Christmas - from its pre-Christian roots, through the birth of Jesus, to the holiday's spread across Europe into the Americas and beyond, and to its mind-boggling transformation through modern consumerism.